A new perspective on poverty in the Caribbean : the strength of a participatory approach - Melville, Juliet (Ian Randle Pub. KingstonJM, 2007)
Examines the characteristics of poverty in the region and reflects on the social policy environment needed to drive the process of poverty reduction. Points to the need for a new perspective on poverty that emphasises the use of both qualitative and quantitative approaches in assessing the extent and nature of poverty.